The American friend - Highsmith, Patricia; Hopper, Dennis, Emilio; Ganz, Bruno; Kreuzer, Lisa; Wenders, Wim; Bavaria Film (Firm). ([Place of distributor not identified] Bavaria Film, 1977)
Tom Ripley has a sweet deal with an art forger. The forger creates the paintings; Tom sells them. But another criminal business associate wants Tom to go in for an even riskier enterprise: murder. Tom suggests his associate ask a local picture framer instead. That man has a fatal disease, or so it's rumored. More, he has a wife and kid that surely he wouldn't want to leave penniless. Let this picture framer be a hit man, and no one will suspect. The terminally ill craftsman may agree to the misdeed, and several more, but he'll end up needing Tom Ripley in a pinch. Written by J. Spurlin
"Summary taken from https://www.imdb.com/title/tt0075675/?ref_=fn_al_tt_3
Produced Wim Wenders ; music by Jurgen Knieper; cinematography by Robby Meller.
Dennis Hopper, Bruno Ganz, Lisa Kreuzer.
DVD
In English.
Keywords: Drama; Crime film; Feature film